2005
DOI: 10.1039/b501834j
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids

Abstract: This review covers the isolation and structures of diterpenoids, including labdanes, clerodanes, pimaranes, abietanes, kauranes, cembranolides, taxanes and marine diterpenoids. The literature from January to December 2004 is reviewed, and 168 references are cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 169 publications
0
14
0
Order By: Relevance
“…However, it appears that IA's activity is more specific to the NF-B pathway, because kaurenes also inhibit the phosphorylation of p38, ERK1, and ERK2 MAPK. Diterpenoids are natural compounds with a backbone of 20 carbon atoms biosynthesized from geranylgeranyl pyrophosphate (Hanson, 2005). It is an important and chemically diverse group of natural products, which share some common biosynthetic steps and are of considerable biological importance (Hanson, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it appears that IA's activity is more specific to the NF-B pathway, because kaurenes also inhibit the phosphorylation of p38, ERK1, and ERK2 MAPK. Diterpenoids are natural compounds with a backbone of 20 carbon atoms biosynthesized from geranylgeranyl pyrophosphate (Hanson, 2005). It is an important and chemically diverse group of natural products, which share some common biosynthetic steps and are of considerable biological importance (Hanson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Diterpenoids are natural compounds with a backbone of 20 carbon atoms biosynthesized from geranylgeranyl pyrophosphate (Hanson, 2005). It is an important and chemically diverse group of natural products, which share some common biosynthetic steps and are of considerable biological importance (Hanson, 2005). It is noteworthy that although members of this group of natural products share no common chemical moiety, a large arsenal of biologically active compounds has been identified among them (see Ojo-Amaize et al, 2002;Tempeam et al, 2005;Zhang et al, 2005 for some examples), and several diterpenoids are known as inhibitors of NF-B activation (Castrillo et al, 2001;Leung et al, 2005;Yinjun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2004). They are part of af amily of al arger class of natural molecules, referred to as labdanes, and for which no mode of action has yet been elucidated (Hanson 2005). Herein, it is demonstrated that these compoundsa re potent inhibitors of eukaryotic translation elongation.T heyc ause accumulation of ribosomes on mRNA templates and interfere with the translocations tep of elongation.…”
Section: Introductionmentioning
confidence: 99%
“…ribosomes fromp olysomes. Chlorolissoclimides are members of alarger family of diterpenoids, called labdanes, that also show significanta ctivity against manye ukaryotic organisms (Hanson 2005). For instance, norditerpenes aldehydes isolated fromt he shrub Vitex trifolia showed potent activity against Trypanosomac ruzi,t he causative agento fA merican trypanosomiasis (Kiuchi et al 2004).…”
Section: Novel Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…A rearrangement of this kind would be required to access the picrasane skeleton quassinoids. This rearrangement would be the opposite of the biosynthetic route, in which the ent-labdanes are the precursors of ent-halimanes [6].…”
Section: Tricyclic Diterpenementioning
confidence: 99%